Research on Spatial Integration Design of Unmanned Aerial Vehicle Facilities in Future Communities under the Background of Low-Altitude Economy: Taking Hangzhou Cloud City as an Example - Zhao, Feng; Xu, Wei (International Journal of Social Sciences and Public Administration, 2026)
The rapid development of the low-altitude economy and the construction of future communities have created an urgent need for the spatial integration of drone facilities and residential buildings. Existing research mainly focuses on airspace management, industrial economics, and technical engineering, while research on the spatial integration of drone landing facilities from the perspective of architecture and urban planning is still lacking. This study proposes the concept of "vertical logistics interface" and constructs a typological framework of "building-drone" interface types such as rooftop, facade, and balcony. Based on the four-dimensional coupling analysis of "drone type-facility-population-policy", it establishes six design principles: technology adaptability, population friendliness, structural safety, spatial embedding, dual-use (normal and emergency), and intelligent interconnection. It proposes a "2+N" distributed network strategy to address the pain points of existing public take-off and landing fields, such as end-point gaps, land occupation, and functional isolation. Taking Hangzhou Yuncheng Hangteng Future Community as an example, the spatial integration design of two rooftop integrated hubs and N building micro-platforms was completed. The pioneering use of balcony retractable landing panels to achieve direct drone delivery indoors was achieved, constructing a three-dimensional integrated logistics network of "underground-ground-low altitude", providing a reference design idea for the construction of future communities in pilot cities of the low-altitude economy.